DECISION SUPPORT SYSTEM APPLICATION FOR SELECTION OF SCHOLARSHIP RECIPIENTS USING MOORA METHOD - Berti Sari Br Sembiring; Mahdianta Pandia; Devanta Abraham Tarigan (INFOKUM, 2022)
Scholarships can be said as funding that does not come from self-funding or parents, but is provided by the government, private companies, embassies, universities, educational or research institutions, or also from the office where one works because of one's achievements can be given the opportunity to increase resource capacity. human resources through education. As for the results of the research, it was obtained by students who received scholarships at STMIK Neumann with a value of 3.0665 ranking 1